Increased reliance on diurnal pollination in a geographically and morphologically atypical sand verbena - Sierra Jaeger; Micah Freedman; Catherine Alexander; Evan Hilpman; Marjorie Weber; Eric LoPresti (Journal of Pollination Ecology)
Premise—Pollinator-mediated selection drives floral morphologies to converge on sets of traits deemed “pollination syndromes”. As a result of similarity due to common descent, pollination syndromes can be shared among closely related plants in cases where pollinators remain relatively constant over evolutionary time. In these cases, species that display trait deviations away from their ancestral states may indicate hidden pollinator shifts. Identifying when and where trait deviations reflect reproductive contributions from unexpected pollinators is important for understanding the boundaries and cohesion of pollination syndrome phenotypes.